Leishmania donovani induced Unfolded Protein Response delays host cell apoptosis in PERK dependent manner - Abhishek, Kumar; Das, Sushmita; Kumar, Ashish; Kumar, Ajay; Kumar, Vinod; Saini, Savita; Mandal, Abhishek; Verma, Sudha; Kumar, Manjay; Das, Pradeep (PLOS Neglected Tropical Diseases, 2018)
Author summary Visceral Leishmaniasis or Kala-azar is one of the severe tropical neglected parasitic diseases caused by Leishmania donovani in Indian subcontinent. Modulation of host in terms of delayed apoptotic induction is one of the aspects which favours disease establishment; however the mechanism is not clearly understood yet. In the present study, we tried to explore the connection between L.donovani infection induced UPR in host with delayed onset of apoptosis. We found that L.donovani infection phosphorylates the PERK and Akt molecule in host along with delayed apoptosis. Simultaneously, the levels of cellular IAP (cIAP1 & 2) genes were also up-regulated in infected macrophages. To assess the involvement of PERK in delayed apoptosis of host, we inhibited the phosphorylation of PERK under the exposure to apoptotic inducers. We found that PERK inhibition decreased the Akt phosphorylation and fails to activate other associated downstream molecules involved in delayed apoptosis of host. Also, a significant reduction in cIAP levels was observed. Under oxidative exposure, inhibition of PERK phosphorylation debilitates infected RAW cell’s ability to maintain redox homeostasis leading to higher nitric oxide production. Altogether, L.donovani infection modulates host apoptosis in a PERK dependent manner and favours infection.